Tendencies and Challenges in Global Agriculture - Késmárki-Gally, Szilvia; Fenyvesi, László (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2012)
The development of global agricultural market has been at the forefront of professional studies. Expert opinions have quite differing views as to whether the world’s food production will be able to supply (and under what circumstances) the huge demand of growing population. Our paper provides a general overview of global agricultural trends, including alternative views on whether agricultural productivity increases will be able to keep up with food demand increases, price trends, and which regions of the world may undergo the largest food demand changes in the future. Our research has focused on the present state of the agricultural market and on the analysis of the key factors defining the tasks the agricultural sector faces in the near future, with a special attention to the case of Hungary.